anonymous
  • anonymous
What am I doing wrong with this problem? f(x)=3sqrt(5-x)+3 y=3sqrt(5-x)+3 3sqrt(5-x)=y-3 (3sqrt(5-x)^3=(y-3)^3 5-x=(y-3)^3 x=-(y-3)^3-5
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
amistre64
  • amistre64
y = 3rt(5-x) + 3 ; i assume you wanna invert it x = (5-y)^(1/3) + 3 x-3 = (5-y)^(1/3) (x-3)^3 = 5-y (x-3)^3 -5 = -y -(x-3)^3 +5 = y
amistre64
  • amistre64
that last part there; you subtracted the 5; then for got to negate it with the /-1
amistre64
  • amistre64
[(x-3)^3 -5 = -y] * -1 -((x-3)^3 -5) = y

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
I see, ok. thank you.
amistre64
  • amistre64
youre welcome :) the other day I did 3*3 = 6 twice in a row and couldnt see for the life of me what i did wrong lol
anonymous
  • anonymous
haha, that kinda week.... Thansk again
anonymous
  • anonymous
Actually, I just checked this answer and wamap isn't happy with this one either.

Looking for something else?

Not the answer you are looking for? Search for more explanations.